Soothing the savage beast : venting rage - Films for the Humanities & Sciences (Firm) (New York, N.Y. : Films Media Group, 2007)
Is the physical release of anger in a controlled setting a healthy way to process it? Many angry people say yes-but not all researchers agree: "It's a seductive theory. It does make sense, but it's a myth," says noted psychologist Dr. Brad Bushman. In this program, ABC News anchors Charles Gibson and Connie Chung and correspondent John Stossel set the record straight about two different anger disorders and the methods used to control them. For under-venters, bataka bats and anger release workshops may be the prescription, but for over-venters, an anger management workshop is a better choice.
Films on Demand is distributed by Films Media Group for Films for the Humanities & Sciences, Cambridge Educational, Meridian Education, and Shopware./ Encoded with permission for digital streaming by Films Media Group on April 04, 2007./ Title from distributor's description./ Audience: 11 & up.
Keywords: Conflict management; Anger -- Prevention